Gradient sintering process of alumina refractory material based on critical temperature control
By using a gradient sintering process based on critical temperature control, a multi-layered gradient structure is formed inside the alumina refractories, solving the problems of corrosion resistance and thermal shock resistance of traditional materials in high-temperature environments, and achieving a significant improvement in material performance.
Patent Information
- Application Number
- CN202511183959.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-14
AI Technical Summary
Traditional alumina refractories are easily corroded by molten slag in high-temperature environments and have poor thermal shock resistance. It is difficult to meet the performance requirements of high strength, corrosion resistance and thermal shock resistance through a single component and uniform structure.
A gradient sintering process based on critical temperature control is adopted. Through multi-stage temperature control and the addition of composite additives such as nano ZrO2, Yb2O3, and Cr2O3, a gradient structure is formed inside the material. Ultrasonic vibration and isostatic pressure are applied at high temperature, combined with segmented nitriding treatment, to form a multi-layer gradient structure to improve the material performance.
It significantly improves the overall performance of the material, including the surface corrosion resistance, the internal thermal shock resistance, and the overall mechanical properties, extending its service life and reducing crack formation.
Smart Images

Figure CN120943654A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alumina functional material preparation technology, specifically to a gradient sintering process for alumina refractory materials based on critical temperature control. Background Technology
[0002] Alumina refractories are widely used in high-temperature industries such as steel, glass, and ceramics due to their excellent high-temperature resistance and chemical stability. However, traditional alumina refractories face several challenges during use. On the one hand, under high-temperature conditions, the material is susceptible to erosion by molten slag, leading to structural damage and a shortened service life. On the other hand, due to temperature fluctuations during industrial production, the material needs to possess good thermal shock resistance to prevent cracking or breakage caused by rapid temperature changes. Traditional sintering processes struggle to create a gradient structure within the material, making it impossible to simultaneously meet the performance requirements of high strength, erosion resistance, and thermal shock resistance.
[0003] With the development of high-temperature industries, higher demands are being placed on the performance of alumina refractories. For example, in processes such as continuous steel casting and RH vacuum refining, refractories need to be exposed to high-temperature environments above 1600℃ for extended periods, while also withstanding the erosion and corrosion of molten steel and slag. Traditional single-component and homogeneous refractories often exhibit insufficient erosion resistance and poor thermal shock stability under these harsh conditions, leading to increased equipment maintenance costs and reduced production efficiency. Therefore, developing a preparation process that can improve the overall performance of alumina refractories has become an urgent technical challenge.
[0004] To improve the performance of traditional alumina refractories, researchers have tried various methods. For example, adding various additives to enhance the material's properties has yielded limited results. Furthermore, traditional sintering processes typically employ a single temperature, making it difficult to create a gradient structure within the material and achieve optimal performance matching. Therefore, a new sintering process is needed that can precisely control parameters such as temperature and atmosphere during sintering to create a gradient structure within the material, thereby improving its overall performance. Summary of the Invention
[0005] (a) Technical problems to be solved
[0006] To address the shortcomings of existing technologies, this invention provides a sunscreen composition and its preparation method.
[0007] (II) Technical Solution
[0008] A gradient sintering process for alumina refractory materials based on critical temperature control, the process comprising the following steps:
[0009] S1 Raw Material Preparation: α-Al₂O₃ powder with a purity ≥99.5%, 1.5-3 wt% nano-ZrO₂, 0.8-2 wt% Yb₂O₃, 0.5-1.5 wt% Cr₂O₃, 0.3-0.8 wt% La₂O₃, and 0.2-0.5 wt% HfO₂ are mixed and deionized water is added to prepare a suspension with a solid content of 65-75 wt%. During sintering, Yb₂O₃ and Cr₂O₃ undergo a solid solution strengthening reaction to generate the composite oxide YbCrO₃, with the reaction formula: Yb₂O₃ + 2Cr₂O₃ → 2YbCrO₃ + Cr₂O. HfO₂ and Al₂O₃ react at high temperature to form HfAl. 18 O 27 Whiskers, the reaction is: 9Al₂O₃ + HfO₂ → HfAl 18 O 27 ;
[0010] S2 molding: The suspension is spray-granulated and isostatically pressed at a pressure of 180-220MPa for 3-5 minutes to obtain a green body.
[0011] S3 critical temperature gradient sintering:
[0012] Low temperature section: Heat to 600-700℃ at 5-8℃ / min and hold for 2-3 hours to remove organic matter from the green body;
[0013] Medium temperature range: Increase the temperature to 1200-1300℃ at 3-5℃ / min and hold for 1-2 hours to promote the formation of solid solution between Cr2O3 and Al2O3 and enhance the grain boundary bonding force;
[0014] High temperature section: The temperature is increased to 1650-1750℃ at 1-3℃ / min and held for 2-4 hours. At this time, Yb2O3 and Cr2O3 undergo a solid solution reaction to form the YbCrO3 reinforcing phase.
[0015] Gradient cooling: The temperature is reduced to 1400℃ at a rate of 2-4℃ / min, and then reduced to room temperature at a rate of 5-10℃ / min to form a grain size gradient structure from the surface to the interior, with a surface grain size of 1-3μm and an interior grain size of 5-10μm.
[0016] S4 Post-treatment: The sintered body is subjected to surface nitriding treatment at a temperature of 1100-1200℃ for 4-6 hours to form an AlN reinforcement layer with a thickness of 10-30μm.
[0017] Preferably, the method further includes adding 0.1-0.3 wt% of graphene nanosheets to the preparation of raw material S1. The graphene nanosheets react in situ with Al2O3 at high temperature to generate Al4C3 nanowires. The reaction formula is: 4Al2O3+3C→2Al4C3+3O2↑.
[0018] Preferably, it also includes applying a frequency of 10-30kHz and a power density of 0.5-2W / cm² in the S3 high-temperature section. 2 The ultrasonic vibration promotes the uniform distribution of the YbCrO3 strengthening phase and inhibits abnormal grain growth.
[0019] Preferably, in the S3 gradient cooling stage, CO2 gas with a volume fraction of 2-5% is introduced in the range of 1400-1200℃ to form an Al2O3-Cr2O3 solid solution protective layer with a thickness of 5-15μm on the surface of the material. The reaction formula is: 2Al2O3+4Cr2O3+3CO2→2(Al2O3·2Cr2O3)+3CO↑. This protective layer can improve the corrosion resistance of the material.
[0020] Preferably, the S4 nitriding treatment adopts a segmented nitriding process: first, nitriding is carried out at 1100-1150℃ for 2-3 hours to form an initial AlN layer; then, the temperature is raised to 1150-1200℃ for nitriding for 2-3 hours to allow the AlN layer to diffuse and grow inward, forming a gradient nitrogen concentration distribution, with a surface nitrogen content of 8-12wt% and an internal nitrogen content of 1-3wt%.
[0021] Preferably, during the spray granulation process, 0.5-1.5 wt% of a composite binder is added. The composite binder is composed of polyvinyl alcohol (PVA) and hydroxypropyl methylcellulose (HPMC) in a mass ratio of 3:1, controlling the sphericity of the particles to ≥95% and the loose density to ≥2.0 g / cm³. 3 .
[0022] Preferably, the isostatic pressing mold adopts a double-layer structure, with the inner layer being fluororubber with a hardness of 70-80 Shore A; and the outer layer being nitrile rubber with a hardness of 60-70 Shore A; the mold has an elastic modulus gradient distribution of 5-15 MPa and a Poisson's ratio of 0.47-0.49.
[0023] Preferably, the sintering process is carried out in a segmented atmosphere: a nitrogen atmosphere is used in the low-temperature to medium-temperature section, and an argon atmosphere is used in the high-temperature section. 0.1-0.5 vol% HCl gas is mixed into the argon gas. The HCl gas reacts with impurities in the material to generate volatile chlorides, reducing the impurity content of the material to ≤0.05 wt%.
[0024] Preferably, the post-treated refractory material forms a five-layer gradient structure:
[0025] Surface layer: AlN reinforced layer, thickness 10-30μm, hardness ≥25GPa;
[0026] Subsurface layer: Al2O3-Cr2O3 solid solution layer, 5-15 μm thick, coefficient of thermal expansion 8.5-9.5 × 10⁻⁶ -6 / ℃;
[0027] Transition layer: An Al2O3 matrix with dispersed YbCrO3 reinforcing phase, 50-100 μm thick, with a fracture toughness ≥6.5 MPa·m. 1 / 2;
[0028] Core layer: HfAl 18 O 27 Whisker-reinforced Al2O3 matrix with thermal conductivity ≥35W / (m·K);
[0029] Inner layer: original Al2O3 matrix, grain size 5-10μm, thermal shock resistance ΔT≥300℃.
[0030] Preferably, when the refractory material is used as the lining of an RH vacuum refining furnace in the steel industry, it exhibits a slag erosion resistance rate of ≤0.05mm / h at 1600℃, no cracks after ≥30 thermal shock cycles, and a service life 2-3 times longer than that of traditional alumina refractory materials.
[0031] (III) Beneficial Technical Effects
[0032] Compared with existing technologies, the beneficial effects of this invention are:
[0033] 1. This process, through multi-stage temperature control and composition design, forms a gradient structure from the surface to the interior of the material, significantly improving its overall performance. Firstly, the gradient structure gives the material surface high hardness and corrosion resistance, effectively resisting slag erosion and extending the material's service life. Secondly, the material's interior exhibits good thermal shock resistance, enabling it to adapt to temperature fluctuations in high-temperature environments and reducing crack formation.
[0034] 2. This process, through the addition of various composite additives, such as nano-ZrO2, Yb2O3, and Cr2O3, induces solid solution strengthening and whisker formation reactions during sintering, further enhancing the material's strength and toughness. Simultaneously, the added graphene nanosheets undergo an in-situ reaction with Al2O3 at high temperatures, generating Al4C3 nanowires that form a three-dimensional network structure within the material, improving its thermal conductivity and thermal shock resistance.
[0035] 3. This process applies ultrasonic vibration and isostatic pressure during sintering, promoting the uniform distribution of the reinforcing phase, inhibiting abnormal grain growth, and forming a fine-grained structure within the material, thereby improving its mechanical properties. The application of segmented nitriding treatment forms an AlN reinforcing layer on the material surface, further improving the material's surface hardness and wear resistance. Attached Figure Description
[0036] Figure 1This invention discloses a process flow diagram for gradient sintering of alumina refractory materials based on critical temperature control.
[0037] Figure 2 This is a graph comparing the fracture toughness and hardness of the embodiments and comparative examples.
[0038] Figure 3 This is a fitting curve of the effect of ultrasonic frequency on the grain size of the material;
[0039] Figure 4 This is a fitted curve showing the effect of nitriding temperature on the thickness of the AlN layer. Detailed Implementation
[0040] according to Figures 1 to 4 The specific embodiments of the present invention are as follows:
[0041] Example 1: Gradient alumina refractory material for continuous casting of steel
[0042] Raw material preparation: 96.2 wt% α-Al2O3 powder, with a median particle size of 3 μm and a purity of 99.7%; 2 wt% nano ZrO2, with a particle size of 50 nm; 1.2 wt% Yb2O3, with a particle size of 70 nm; 0.8 wt% Cr2O3, with a particle size of 2 μm; 0.5 wt% La2O3, with a particle size of 40 nm; 0.3 wt% HfO2, with a particle size of 60 nm; 0.1 wt% graphene nanosheets, with a sheet diameter of 10 μm and a thickness of 3 nm.
[0043] Deionized water and 0.8 wt% composite binder, which is a mixture of PVA and HPMC at a mass ratio of 3:1, were added. The mixture was ball-milled for 12 hours to obtain a suspension with a solid content of 70 wt%.
[0044] Molding: The suspension is spray-granulated with an inlet air temperature of 220℃ and an outlet air temperature of 100℃ to obtain a sphericity of 96% and a bulk density of 2.1 g / cm³. 3 granules.
[0045] Isostatic pressing was performed using a double-layer rubber mold. The inner layer was made of fluororubber with a hardness of 75 Shore A, and the outer layer was made of nitrile rubber with a hardness of 65 Shore A. The molding pressure was 200 MPa, and the holding time was 4 minutes.
[0046] Critical temperature gradient sintering: In the low-temperature stage, the temperature is increased to 650℃ at a rate of 6℃ / min, maintained under a nitrogen atmosphere (99.99% purity), and held for 2.5 hours. In the medium-temperature stage, the temperature is increased to 1250℃ at a rate of 4℃ / min and held for 1.5 hours. This stage promotes the formation of a solid solution between Cr₂O₃ and Al₂O₃. In the high-temperature stage, the temperature is increased to 1700℃ at a rate of 2℃ / min, switched to an argon atmosphere containing 0.3 vol% HCl, and held for 3 hours. A power density of 1.2 W / cm² is applied simultaneously during this holding period.2 The ultrasonic vibration.
[0047] Gradient cooling: First, cool down to 1400℃ at a rate of 3℃ / min, during which 3 vol% CO2 atmosphere is introduced and an isostatic pressure of 15 MPa is maintained; after reaching 1400℃, cool down to room temperature at a rate of 8℃ / min.
[0048] Post-treatment (segmented nitriding):
[0049] First stage: Nitriding treatment at 1120℃ for 2.5 hours, controlling the NH3 decomposition rate to 50%.
[0050] Second stage: Nitriding treatment at 1180℃ for 2.5 hours, controlling the NH3 decomposition rate to 60%.
[0051] This process forms an AlN reinforcement layer with a thickness of approximately 20 μm.
[0052] Example 2: High-performance refractory material for RH vacuum refining furnace
[0053] Raw material preparation: 95.5wt% α-Al2O3 powder, with a median particle size of 4μm and a purity of 99.8%; 2.5wt% nano ZrO2, with a particle size of 60nm; 1.5wt% Yb2O3, with a particle size of 80nm; 1.0wt% Cr2O3, with a particle size of 1.5μm; 0.6wt% La2O3, with a particle size of 50nm; 0.3wt% HfO2, with a particle size of 70nm; 0.2wt% graphene nanosheets.
[0054] Add deionized water and 1.0 wt% composite binder, and ball mill the mixture for 15 hours to obtain a suspension with a solid content of 72 wt%.
[0055] Molding: Suspension spray granulation, inlet air temperature 230℃, outlet air temperature 110℃, yielding a sphericity of 97% and a bulk density of 2.2 g / cm³. 3 granules.
[0056] Isostatic pressing, pressure 210MPa, holding time 5 minutes.
[0057] Critical temperature gradient sintering:
[0058] Low temperature section: Increase the temperature to 680℃ at a rate of 7℃ / min and hold for 3 hours.
[0059] Medium temperature range: Heat to 1280℃ at a rate of 4.5℃ / min and hold for 2 hours.
[0060] High-temperature section: The temperature is increased to 1720℃ at a rate of 2.5℃ / min, and held in an argon atmosphere (containing 0.4 vol% HCl) for 3.5 hours, while applying an argon gas with a frequency of 25 kHz and a power density of 1.5 W / cm³. 2 The ultrasonic vibration.
[0061] Gradient cooling: The temperature was reduced to 1400℃ at a rate of 3.5℃ / min, during which 4 vol% CO2 was introduced and an isostatic pressure of 18 MPa was maintained; after reaching 1400℃, the temperature was reduced to room temperature at a rate of 9℃ / min.
[0062] Post-treatment (segmented nitriding):
[0063] First stage: Nitriding at 1130℃ for 2 hours, NH3 decomposition rate 55%.
[0064] Second stage: Nitriding at 1190℃ for 3 hours, NH3 decomposition rate 65%.
[0065] An AlN reinforcement layer with a thickness of approximately 25 μm was formed.
[0066] Example 3: Erosion-resistant refractory material for glass furnaces
[0067] Raw material preparation: 95.0 wt% α-Al2O3 powder, with a median particle size of 2.5 μm and a purity of 99.9%; 3.0 wt% nano ZrO2, with a particle size of 40 nm; 1.8 wt% Yb2O3, with a particle size of 60 nm; 1.2 wt% Cr2O3, with a particle size of 1 μm; 0.7 wt% La2O3, with a particle size of 30 nm; 0.2 wt% HfO2, with a particle size of 50 nm; 0.1 wt% graphene nanosheets.
[0068] Add deionized water and 1.2 wt% composite binder, and ball mill the mixture for 18 hours to obtain a suspension with a solid content of 75 wt%.
[0069] Molding: Suspension spray granulation, inlet air temperature 240℃, outlet air temperature 120℃, yielding a sphericity of 98% and a bulk density of 2.3 g / cm³. 3 granules.
[0070] Isostatic pressing, pressure 220MPa, holding time 3 minutes.
[0071] Critical temperature gradient sintering:
[0072] Low temperature section: Increase the temperature to 700℃ at a rate of 8℃ / min and hold for 2 hours.
[0073] Medium temperature range: Increase the temperature to 1300℃ at a rate of 5℃ / min and hold for 1 hour.
[0074] High-temperature section: The temperature is increased to 1750℃ at a rate of 3℃ / min, and held in an argon atmosphere (containing 0.5 vol% HCl) for 4 hours, while applying a power density of 2.0 W / cm³ at a frequency of 30 kHz. 2 The ultrasonic vibration.
[0075] Gradient cooling: The temperature was reduced to 1400℃ at a rate of 4℃ / min, during which 5 vol% CO2 was introduced and an isostatic pressure of 20 MPa was maintained; after reaching 1400℃, the temperature was reduced to room temperature at a rate of 10℃ / min.
[0076] Post-treatment (segmented nitriding):
[0077] First stage: Nitriding at 1150℃ for 2 hours, NH3 decomposition rate 60%.
[0078] Second stage: Nitriding at 1200℃ for 2 hours, NH3 decomposition rate 70%.
[0079] An AlN reinforcement layer with a thickness of approximately 30 μm is formed.
[0080] Comparative Example: Traditional Alumina Refractory Material Preparation Process
[0081] Raw material preparation: 98wt% of α-Al2O3 powder (median particle size 5μm) is mixed with 2wt% of SiO2-MgO composite additive, and a binder is added to make slurry.
[0082] Molding: Machine pressing was used at a pressure of 100 MPa, resulting in a blank density of 2.8 g / cm³. 3 .
[0083] Sintering: Heat to 1600℃ at 5℃ / min, hold at that temperature for 4 hours in air atmosphere, and then cool with the furnace.
[0084] The performance comparison between the examples and the comparative examples is shown in the table below:
[0085] Table 1
[0086] project Example 1 Example 2 Example 3 Comparative Example Hardness (GPa) 26.3 27.1 28.5 18.5 <![CDATA[Fracture toughness (MPa·m 1 / 2)]]> 7.2 7.8 8.3 4.1 <![CDATA[Coefficient of thermal expansion (×10 -6 / °C)]]> 7.8 8.9 9.2 8.9 Thermal shock resistance (secondary) 35 38 42 5 Erosion resistance rate (mm / h) 0.03 0.04 0.02 0.2
[0087] The effect of ultrasonic frequency on material grain size is shown in the table below:
[0088] Table 2
[0089] Ultrasonic frequency (kHz) Surface grain size (μm) Internal grain size (μm) 0 5 12 10 3.5 8 20 3 6 30 2.8 5.5
[0090] The effect of nitriding temperature on AlN layer thickness is shown in the table below:
[0091] Table 3
[0092]
[0093]
[0094] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A gradient sintering process for alumina refractory materials based on critical temperature control, characterized in that, The process includes the following steps: S1 Raw Material Preparation: α-Al₂O₃ powder with a purity ≥99.5%, 1.5-3 wt% nano-ZrO₂, 0.8-2 wt% Yb₂O₃, 0.5-1.5 wt% Cr₂O₃, 0.3-0.8 wt% La₂O₃, and 0.2-0.5 wt% HfO₂ are mixed and deionized water is added to prepare a suspension with a solid content of 65-75 wt%. During sintering, Yb₂O₃ and Cr₂O₃ undergo a solid solution strengthening reaction to generate the composite oxide YbCrO₃, with the reaction formula: Yb₂O₃ + 2Cr₂O₃ → 2YbCrO₃ + Cr₂O. HfO₂ and Al₂O₃ react at high temperature to form HfAl. 18 O 27 Whiskers, the reaction is: 9Al₂O₃ + HfO₂ → HfAl 18 O 27 ; S2 molding: The suspension is spray-granulated and isostatically pressed at a pressure of 180-220MPa for 3-5 minutes to obtain a green body. S3 critical temperature gradient sintering: Low temperature section: Heat to 600-700℃ at 5-8℃ / min and hold for 2-3 hours to remove organic matter from the green body; Medium temperature range: Increase the temperature to 1200-1300℃ at 3-5℃ / min and hold for 1-2 hours to promote the formation of solid solution between Cr2O3 and Al2O3 and enhance the grain boundary bonding force; High temperature section: The temperature is increased to 1650-1750℃ at 1-3℃ / min and held for 2-4 hours. At this time, Yb2O3 and Cr2O3 undergo a solid solution reaction to form the YbCrO3 reinforcing phase. Gradient cooling: The temperature is reduced to 1400℃ at a rate of 2-4℃ / min, and then reduced to room temperature at a rate of 5-10℃ / min to form a grain size gradient structure from the surface to the interior, with a surface grain size of 1-3μm and an interior grain size of 5-10μm. S4 Post-treatment: The sintered body is subjected to surface nitriding treatment at a temperature of 1100-1200℃ for 4-6 hours to form an AlN reinforcement layer with a thickness of 10-30μm.
2. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, It also includes adding 0.1-0.3 wt% of graphene nanosheets to the S1 raw material formulation. The graphene nanosheets react in situ with Al2O3 at high temperature to generate Al4C3 nanowires. The reaction formula is: 4Al2O3+3C→2Al4C3+3O2↑.
3. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, This also includes applying a frequency of 10-30kHz and a power density of 0.5-2W / cm² in the S3 high-temperature section. 2 The ultrasonic vibration promotes the uniform distribution of the YbCrO3 strengthening phase and inhibits abnormal grain growth.
4. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, During the S3 gradient cooling stage, CO2 gas with a volume fraction of 2-5% is introduced in the range of 1400-1200℃, causing a 5-15μm thick Al2O3-Cr2O3 solid solution protective layer to form on the surface of the material. The reaction formula is: 2Al2O3+4Cr2O3+3CO2→2(Al2O3·2Cr2O3)+3CO↑. This protective layer can improve the material's resistance to corrosion.
5. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, In the S4 nitriding treatment, a segmented nitriding process is adopted: first, nitriding is carried out at 1100-1150℃ for 2-3 hours to form an initial AlN layer; then, the temperature is raised to 1150-1200℃ for 2-3 hours to allow the AlN layer to diffuse and grow inward, forming a gradient nitrogen concentration distribution, with a surface nitrogen content of 8-12wt% and an internal nitrogen content of 1-3wt%.
6. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, During the spray granulation process, 0.5-1.5 wt% of a composite binder is added. This composite binder is composed of polyvinyl alcohol (PVA) and hydroxypropyl methylcellulose (HPMC) in a mass ratio of 3:1, controlling the sphericity of the particles to ≥95% and the loose density to ≥2.0 g / cm³. 3 .
7. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, The isostatic pressing mold adopts a double-layer structure. The inner layer is made of fluororubber with a hardness of 70-80 Shore A; the outer layer is made of nitrile rubber with a hardness of 60-70 Shore A. The mold has an elastic modulus gradient distribution of 5-15 MPa and a Poisson's ratio of 0.47-0.
49.
8. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, The sintering process is carried out in a segmented atmosphere: nitrogen atmosphere is used in the low temperature to medium temperature section, and argon atmosphere is switched in the high temperature section. 0.1-0.5 vol% HCl gas is mixed into the argon gas. The HCl gas reacts with impurities in the material to generate volatile chlorides, reducing the impurity content of the material to ≤0.05 wt%.
9. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, The post-treated refractory material forms a five-layer gradient structure: Surface layer: AlN reinforced layer, thickness 10-30μm, hardness ≥25GPa; Subsurface layer: Al2O3-Cr2O3 solid solution layer, 5-15 μm thick, coefficient of thermal expansion 8.5-9.5 × 10⁻⁶ -6 / ℃; Transition layer: Al2O3 matrix with YbCrO3 reinforced phase dispersedly, thickness 50-100μm, fracture toughness ≥6.5MPa·m1 / 2; Core layer: HfAl 18 O 27 Whisker-reinforced Al2O3 matrix with thermal conductivity ≥35W / (m·K); Inner layer: original Al2O3 matrix, grain size 5-10μm, thermal shock resistance ΔT≥300℃.
10. The gradient sintering process for alumina refractory materials based on critical temperature control according to claim 1, characterized in that, When the refractory material is used as the lining of an RH vacuum refining furnace in the steel industry, it exhibits a slag erosion resistance rate of ≤0.05mm / h at 1600℃, no cracks after ≥30 thermal shock cycles, and a service life 2-3 times longer than that of traditional alumina refractory materials.
Citation Information
Cited By
Special coating for lost foam of motor casing as well as preparation method and application of special coating
CN121423526A